Combined targeting of PRDX6 and GSTP1 as a potential differentiation strategy for neuroblastoma treatment - Judit Liaño-Pons; Elisa Garde-Lapido; Fenja L. Fahrig; Merle Jäckering; Ye Yuan; Stina Andersson; Lea Schort; Maria Esteve; Sofie Mohlin; Oscar C Bedoya-Reina; Marie Arsenian-Henriksson (Proceedings of the National Academy of Sciences, 2025)
Neuroblastoma (NB) is a heterogeneous childhood cancer, characterized by the amplification of the MYCN oncogene in 40% of the high-risk cases. Our previous work demonstrated that MYCN drives metabolic reprogramming in NB, including upregulation of antioxidant enzymes. Here, we identify peroxiredoxin 6 (PRDX6) as a promising therapeutic target in NB. Pharmacological inhibition of PRDX6 reduces MYCN levels, induces apoptosis, and promotes neuronal differentiation accompanied by lipid droplet accumulation, essential for the phenotypic reprogramming. Moreover, combined inhibition of PRDX6 and glutathione S-transferase Pi 1 (GSTP1), a key antioxidant enzyme needed for PRDX6 activation, demonstrated synergistic effects both in vitro and in vivo. This strategy results in neuronal maturation and initiates downstream pathways distinct from the ones triggered by retinoic acid, the differentiation-inducing agent currently used in clinical practice for NB. Notably, both PRDX6 and GSTP1 are highly expressed in the developing murine adrenal gland, as well as in high-risk, MYCN -amplified NB, correlating with an undifferentiated state and poor prognosis. Together, our results provide insights into the potential of PRDX6 and GSTP1 as therapeutic targets for differentiation induction for children with NB.